Pathologic findings in reduction mammaplasty specimens: a South African perspective - Sofianos, Chrysis (My University, 2018)
Background Preoperative, intraoperative and follow-up guidelines for managing occult carcinoma in reduction mammoplasty specimens are scant. Methods We retrospectively analysed the records and pathology reports of 200 patients who had undergone reduction mammoplasty at two major public hospitals in Johannesburg, South Africa, during 2009 - 2014. Demographic data, their history of breast cancer and preoperative screening, and the surgical techniques used and pathological reports were included. In all cases, preoperative screening for breast cancer had been negative. Results All the patients were female, mean age 37.1 years, range 20 - 84 (standard deviation 11.9). All reductions were performed using standard techniques. Benign pathology was observed in 98 patients (49%) and malignant pathology in four (2%). The most common benign pathology observed was fibrocystic disease, and the most common malignant pathology ductal carcinoma in situ. Patient age correlated significantly with benign or malignant disease. Conclusions Reduction mammoplasty produces tissue that should always be sent for pathological assessment. Patients should be stratified by risk, as doing so helps in selecting both the surgical setting and the approach to pathological analysis of the specimen. While the Pathologic findings in reduction mammaplasty specimens: A South African perspective incidence of occult carcinoma in reduction mammoplasty specimens is low, all patients undergoing the procedure should be informed that tissue will be sent for pathological examination, allowing them to prepare to receive possible news of breast cancer and be adequately equipped for subsequent decision-making.
Keywords: Mammaplasty; Carcinoma